Activated Hydrotalcites Obtained by Coprecipitation as Photocatalysts for the Degradation of 2, 4, 6-Trichlorophenol. (2nd December 2018) - Ramos-Ramírez, Esthela; Gutiérrez-Ortega, Norma; Tzompantzi, Francisco; Gómez, Claudia M.; del Angel, Gloria; Herrera-Pérez, Gabriel; Serafín-Muñoz, Alma Hortensia; Tzompantzi-Flores, Clara
Abstract : A gallery of hydrotalcite-type mesoporous materials with different Mg/Al molar ratios were synthesized by the coprecipitation method. The materials were activated by heat treatment to test their activity in the photodegradation of 2, 4, 6-trichlorophenol under UV light irradiation. The physicochemical properties of the different synthesized and activated materials were determined using XRD, physical adsorption/desorption of N2, FTIR, SEM, DTA, and TGA. Their banned band energy was determined by UV-Vis to identify their potential to be used as a semiconductor in catalytic photodegradation processes. The results of photodegradation tests of 2, 4, 6-trichlorophenol showed that hydrotalcites have a high degradation capacity, up to 100% for the catalyst of Mg/Al ratio = 2, with a high mineralization capacity of 80%. The degradation capacity of most of the catalysts tested is mainly due to the presence of holes and the formation of superoxide free radicals, which are the determining species within the degradation mechanism.